The Relationship between Permanent Income and Measured Variables - Arak, M. V.; Spiro, Alan (Journal of Political Economy, 1971)
We demonstrate that if consumption is proportional to permanent income, it is necessarily equal to a geometrically weighted average of past realized incomes. Therefore, the relationship between consumption and measured income depends entirely upon the linkage between realized and measured income. Two hypotheses concerning the linkage are tested against 1929-62 U.S. data. The relationship implied by Friedman is not found to be significant, whereas a new hypothesis that the difference between realized and measured income depends upon changes in the unemployment rate does yield significant results.